Los créditos del sistema financiero y la evolución de la economía del departamento de Loreto periodo 2018 – 2022 - Celis Guerra, Aida Rosana del Pilar (2024)
Credit is a fundamental tool that boosts production, giving greater activity to the economy, as it fulfills its dynamic role as a whole productive factor. In this master's thesis, the evolution of the economy is measured through the behavior of the Gross Value Added (GVA). The objective of this research is to determine the relationship between the credits of the financial system and the evolution of the economy of the department of Loreto, in the period 2018 - 2022. Due to this, the Quantitative study is carried out, Correlational level and Non-Experimental design. The conclusions reached are: the credits of the financial system are not associated nor do they determine the evolution of the economy of the department of Loreto in the period 2018 - 2022, since the Correlation Coefficient was r = 0.334022142; and the Coefficient of Determination R2 = 0.111570791, well below the minimum required values. The financial entity that placed the largest amount of credits was Banca Multiple with an average balance of S/. 1,574.00 million (62.52%). The delinquency rate of the Commercial Bank remained around 9.00%; above the average delinquency of the system which was 7.96%. It should be noted that the Agrobanco maintained an average delinquency rate of 91.62%. The economic activity Exploitation of Oil, Gas and Minerals was the one that contributed the most to the departmental product with S/. 1,626.11 million (18.24%).